Dissecting the COVID19 supply shock: Which role did school closures play? Lessons from unique survey data in Germany - Sebastian Dullien; Bettina Kohlrausch (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2021)
We use unique survey data on working time reduction during the first wave of the COVID-19 crisis in the spring of 2020 to estimate the number of working hours lost in Germany due to closed schools and child care facilities. Our results indicate that overall, a loss of not more than 1.1 percent of aggregate working hours in April 2020 (at the height of social distancing) and not more than 0.5 percent of aggregate working hours in June 2020 can be attributed to shuttered schools and child care facilities, with a more exact, OLS-based estimate being less than half this size. The upper levels of hours lost because of child-care needs are thus between 5 and 7.5 percent of total hours lost during these crisis months. This is by a factor 8 to 20 less than what has been previously estimated without microeconomic data. This surprisingly low number of actual hours lost is most likely due to flexibility both on the side of the families and on the side of the workplaces which have increasingly allowed employees to choose their own working hours.
Keywords: 330; Coronavirus; Infektionskrankheit; Infektionsschutz; Schule; Kinderbetreuungseinrichtung; Arbeitszeit; Kleinste-Quadrate-Methode; Deutschland